Analisis Rasio Keuangan Untuk Menilai Kinerja Hotel Ciater Spa & Resort, Subang - Saepudin, Pudin; Muslim, Syaeful (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
Financial ratio analysis of a company is one of financial performance assessment that are very useful to management in making plan for both short term and long term. The purpose of this research is to evaluate the implementation of financial statement analysis carried out by Hotel Ciater Spa & Resort in 2013 and 2014. The research method used is descriptive method. From the results of analysis show that the level of liquidity ratios, solvency, and operational is quite high, while the ratio of profitability has. fluctuated and the ratio of the activity has not been fully effective.